Strengthening Early Childhood Teachers’ Capacity through the Implementation of Conflict Resolution Learning to Enhance Children’s Social Skills - Dian Tri Utami; Raihana Raihana; Amiruddin Amiruddin; Ak Muhd Aliman Alim (Journal of Comunity Service in Early Childhood Education, 2025)
Background: Social skills are a fundamental aspect of early childhood development, encompassing communication, empathy, self-control, responsibility, and cooperation. However, many early childhood education practices still tend to be teacher-centered and have not optimally utilized children’s conflicts as opportunities for social learning. In addition, teachers often lack the knowledge and skills to manage peer conflicts constructively in classroom settings. Aims: This community service program aims to strengthen early childhood teachers’ capacity in implementing conflict resolution techniques to enhance children’s social skills. Methods: The program employed an action research approach consisting of planning, action, observation, and reflection stages. The implementation included socialization, training, simulation, and mentoring activities for early childhood teachers. Supporting learning tools such as training modules, daily lesson plans, storybooks, and emotion cards were provided to facilitate the application of conflict resolution strategies in classroom practices. Data were collected through pre-test, post-test, observation, and documentation, and analyzed descriptively. Results: The results indicate a significant improvement in teachers’ understanding and skills in managing children’s conflicts constructively. The average score increased from 46.2% in the pre-test to 86.0% in the post-test. Teachers demonstrated better ability to design and implement conflict resolution-based learning activities. In addition, children showed improved social skills, including communication, empathy, emotional regulation, cooperation, and problem-solving abilities. The use of learning media such as storybooks and emotion cards also supported children’s understanding of emotions and conflict situations. Conclusion: The program effectively strengthens teachers’ capacity in implementing conflict resolution learning and contributes to the improvement of children’s social skills. The integration of training, practical application, and mentoring provides a meaningful and applicable model for enhancing social-emotional learning in early childhood education.